All‐Dielectric Nanophotonics: The High‐Order Toroidal Moments and Anapole States in All‐Dielectric Photonics (Laser Photonics Rev. 13(5)/2019). Issue 5 (8th May 2019) - Gurvitz, Egor A.; Ladutenko, Konstantin S.; Dergachev, Pavel A.; Evlyukhin, Andrey B.; Miroshnichenko, Andrey E.; Shalin, Alexander S.
Abstract : In article number1800266, Egor A. Gurvitz and co‐workers reveal and investigate in detail the high‐order toroidal moments provided by particular "poloidal" current configurations. Therefore, the wire coiled around a torus surface (bottom left) depicts the currents inside a spherical nanoparticle corresponding to a toroidal electric dipole moment. The composition of these coils arranged on the torus surface (center) visualizes a toroidal magnetic moment. Utilizing these two basic configurations, higher‐order toroidal moments may be designed, such as toroidal quadrupoles, octupoles, etc.